2016
DOI: 10.1038/leu.2016.293
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligase Cbl-b activates the p53 pathway by targeting Siva1, a negative regulator of ARF, in FLT3 inhibitor-resistant acute myeloid leukemia

Abstract: Previous clinical studies have shown that the presence of receptor tyrosine kinase (RTK) FLT3 with activating mutation, FLT3-ITD (internal tandem duplication), translates into poor prognosis in acute myeloid leukemia (AML). 1 Several tyrosine kinase inhibitors (TKIs) of constitutively active FLT3 have been developed and tested in clinical trials. 1 So far, these small molecule inhibitors have resulted in only modest improvement in AML patients because of, in part, the presence of leukemic blasts showing resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…TP53 pathway mutations are mutually exclusive with FLT3 mutations in de novo AML and were shown to be related to FLT3 inhibitor resistance 34,35 . Interestingly, we observed one TP53 mutation and one PPM1D mutation that co-occurred with FLT3 -ITD and/or FLT3 TKD in two individual patients with crenolanib poor response.…”
Section: Resultsmentioning
confidence: 99%
“…TP53 pathway mutations are mutually exclusive with FLT3 mutations in de novo AML and were shown to be related to FLT3 inhibitor resistance 34,35 . Interestingly, we observed one TP53 mutation and one PPM1D mutation that co-occurred with FLT3 -ITD and/or FLT3 TKD in two individual patients with crenolanib poor response.…”
Section: Resultsmentioning
confidence: 99%
“…MDM2 inhibits p53 activity in the cytoplasm, promotes p53 degradation and prevents p53 from entering the nucleus and exerts its function [ 45 ]. Moreover, previous studies reported that Cbl-b could target Siva 1 and upregulate p53 in lymphoma [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a protective mechanism preserving p53 levels was demonstrated in acute myeloid leukemia: E3 ubiquitin ligase Cbl-b ubiquitinates Siva-1 leading to its degradation and stabilization of p53 levels. 40 , 41 Further, Siva-1 has a specific p53-independent function in the monoubiquitination of PCNA (proliferating cell nuclear antigen). It binds E3 ubiquitin ligase RAD18 and promotes its E3 PCNA ligase activity.…”
Section: Siva-1 Is An Arf E3 Ubiquitin Protein Ligasementioning
confidence: 99%